The process of learning a second language in esports. - Postigo Fuentes, Ana Yara; Fernández Navas, Manuel (Círculo de Lingüística Aplicada a la Comunicación, 2020)
The importance that videogame industry has gained in different countries and the possibility of playing these videogames online have allowed Spanish players to communicate with players that speak a different language from theirs. In this case of study, the objective has been analysing the process of learning a foreign language when playing videogames, focusing particularly on esports. Observations and analysis of the oral output during gaming, interviews with players and assessment of skills have been carried out to collect information. The results reflect the influence of mandatory communication, learning through interaction and the relationship between learning through videogames and the contents in the classroom as key factors in this process.
Keywords: foreign language; videogames; communicative skills; esports